Peran dan Fungsi Kader HMI dalam Transformasi Perubahan Sosial Masyarakat - Nosman (STAI DDI Kota Makassar, 2020)
This research aims: (1) To describe the roles and functions of an HMI cadre in the transformation of social change in society. (2) Describe what things HMI can do in maximizing its role and function in society. This research method uses a literature study that is carried out to support the course of writing from the beginning to the final preparation of this paper. In addition, a literature study was carried out in order to obtain a strong theoretical basis related to this article so that it can be a reference in carrying out the discussion. Literature studies include collecting data and information from books and journals that have relevance to the discussion in this journal, as well as input from seniors and their comrades in arms at HMI.